Observations on the trawl-fisheries of the Bombay and Saurashtra waters, 1949-50 to 1954-55 - Jayaraman, R; Seshappa, G; Mohamed, K H; Bapat, S V (Indian Journal of Fisheries, 2016)
A historical account of trawling experiments made in Indian waters before the Second World War is given by Chidambaram (1953). Of these, the Bombay waters were covered by S. T. Premier in the year 1900, S. T. William Carrick in 1921-22 and S. T. Madras in 1923. The results of working of S. T. William Carrick are available in the excellent report of Hefford (1949) while those of S. T. Premier and S. T. Madras have not been published. The outcome of these initial trials was not encouraging and it was felt that trawling might not prove economically successful in the areas worked. A reliable picture was, however, obtained of the different species of fishes occurring in these waters during different seasons of a single year.